The New Frontiers of Organic and Composite Nanotechnology - Erokhin V. Victor (Amsterdam, Elsevier, 2008)
This book is an attempt to illustrate current status of modern nanotechnology. The book is divided into 3 main sections, introduction and conclusion. The introduction describes general questions of the problem and main lines of the research activities. In the first section methods of the nanostructures construction are described. Second section is dedicated to the Structure-property relationship. Special attention is paid to the description of the most powerful experimental methods and tools used in nanotechnology, such as probe microscopies, spectroscopied, and scattering methods, including the utilization of synchrotron radiation facilities. The third section describes the applications of nanotechnology in electronics, biotechnology and diagnostics. Conclusion part presents a summary of the status of works in this area and gives some perspectives of the further development.